A fluorescence-based assay for measuring the redox potential of 5-lipoxygenase inhibitors. - Sangchul Lee; Youngsam Park; Junghwan Kim; Sung-Jun Han (PLoS ONE, 2014)
The activities and side effects of 5-lipoxygenase (5-LO) inhibitors can be predicted by identifying their redox mechanisms. In this study, we developed a fluorescence-based method to measure the redox potential of 5-LO inhibitors and compared it to the conventional, absorbance-based method. After the pseudo-peroxidase reaction, the amount of remaining lipid peroxide was quantified using the H2DCFDA (2',7'-dichlorodihydrofluorescein diacetate) fluorescence dye. Our method showed large signal windows and provided comparable redox potential values. Importantly, the redox mechanisms of known inhibitors were accurately measured with the fluorescence assay, whereas the conventional, absorbance-based method showed contradictory results. Our findings suggest that our developed method is a better alternative for classifying the redox potential of 5-LO inhibitors, and the fluorescence assay can be effectively used to study the mechanisms of action that are related to redox cycling.